Civil Law Review Non-performing Loan Settlement Loans Revolving Funds National Program for Community Empowerment in Urban - Ebit Rudianto; Mohammad Roesli (Faculty of Law, Merdeka University Surabaya, Indonesia, 2019)
The purpose of this research is to find out the process of implementing revolving fund loans to PNPMMP and how the settlement of problem loans in revolving fund loans under PNPMMP in terms of the credit agreement law and guarantee law. The problem is the process of implementing PNPMMP revolving loan funds, the obstacles encountered in the process of revolving fund lending and the settlement of problem loans in PNPMMP revolving loan loans in terms of the credit agreement law and guarantee law. The method used in the writing of this thesis is a normative juridical research method and is supported by a descriptive empirical juridical research method, which expresses legislation relating to implementation in society which is the object of research. The lending goes through several stages namely the loan application stage, the inspection stage, the decision stage, and the loan realization stage. This revolving fund loan is very large, felt useful in helping the progress of people's economic life but is not always going well and smoothly, delinquent loans become a common obstacle in the process of lending because revolving non-current funds into problem loans due to KSM defaults due to substandard debtor business, one of KSM members do not make loan repayments, the joint responsibility system is not implemented. Settlement of problem loans is resolved through deliberation and through 3 approaches, namely collecting arrears, rescuing non-performing loans (rescheduling, reconditioning and restructuring) and billing through legal channels.